REGIONAL AUTONOMY IN THE POLITICAL SYSTEM AND AUTHORITY IN INDONESIA - Abdul Rahman Sabara (Fakultas Hukum, Universitas Diponegoro, 2022)
This article examines how the Regional Autonomy in the Political System and Authority in Indonesia. Political System and Authority in Indonesia greatly influence the implementation of the Regional Autonomy in Indonesia. When the Political System and Authority are more directed towards centralized control, the implementation of the Regional Autonomy will weaken, conversely when division of authority from the central government to the regions occurs, the Regional Autonomy should function according to the principle of decentralization. When the position of the Regional Autonomy strengthens, euphoria of the elites in the regions would emerge. With the increase of regional sentiment and ethnocentrism local kings and various other bad effects would also arise.The implementation of the Regional Autonomy should function optimally if the Political System and Authority work in equilibrium, when the central and regional elites have the same focus and orientation on the welfare and social justice for all people of Indonesia.